Sensor Based Algorithm for Self-Navigating Robot Using Internet of Things (IoT) - Helshani, Laurik; Qarkaxhija, Jusuf; Prevalla, Blerta (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Abstract— The purpose of this paper is to show the design technique and programming of an autonomous robot prototype that can go to a predetermined location and return to its starting place utilizing the Global Positioning System (GPS). An HD camera along with an ultrasonic sensor and two IR sensors is used to provide necessary data from the real world to the robot to avoid obstructions, by following GPS Waypoints. A smart algorithm was introduced for path planning and re-planning. The robot can modify its direction using a digital compass reading and input from sensors by computing the heading angle from the current GPS point. This self-navigation mobile robot’s accuracy was evaluated in several locations and is quantified in terms of heading angle and path length from the starting point to the goal point.